Anachronisms in Charles Dickens’s ‘Great Expectations’: A Case Study Based on Gerard Genette’s Structural Narratology - Hilles, Rajaa Radwan (Journal of Humanities & Social Sciences, 2021)
This paper deals with the narrative order of time in Charles Dickens’s novel Great Expectations. Time is crucial in narratological structure as it establishes a logical relation for events in the narrative. Besides, a narrative develops its point of view through the voices in the narrative. This point of view is called focalization. This paper assumes that the sequence of events in Dickens’s Great Expectations does not follow a linear order and consequently, the point of focalization changes throughout the narrative. Accordingly, the current paper intends to investigate the order of narration in the novel. It intends to explore the ultimate thematic concern of the novel as well. The discussion will be in the light of Gerard Genette’s narratological structure and will be applied on Dickens’s Great Expectations. It is the 13th novel in his independent literary works. It has been published unillustrated in 36 weekly instalments in All the Year Round from 1860 through 1861. Then, it has been published in three volumes by Chapman & Hall in1861. The narrative voice has a great impact on the story’s timeline and on the readers because it is narrated in the first-person voice by the protagonist, Philip Pirrip. (Davis, 2007: P 126) The analysis is based on Genette’s theorization of time order in telling a story and communicating a broader point of view that the author intends to make throughout the whole narrative structure.